Knee Ligament Injuries Extraarticular Surgical Techniques - Rossi, Roberto; Margheritini, Fabrizio (Springer Milan : Imprint: Springer, 2014)
Knee ligament injuries are very common and are frequently sports related, although they may arise from trauma experienced during everyday activities. This book provides in-depth descriptions of the extra articular surgical techniques that may be employed when performing ligament reconstruction in patients with injuries involving the posterolateral and posteromedial corners of the knee. It is intended as a practical, "how to" manual that will be of value for both the trainee and the more experienced surgeon. Many of the techniques relate to the central pivot of the knee, i.e. the anterior and posterior cruciate ligaments. For each technique, indications, presurgical planning, postsurgical follow-up and complications are discussed in addition to the surgical details. Numerous tips and pearls are provided and the techniques are clearly depicted in informative high-quality illustrations.